2013
DOI: 10.1186/1741-7015-11-166
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatments in ARDS; a state-of-the-art update

Abstract: Despite its high incidence and devastating outcomes, acute respiratory distress syndrome (ARDS) has no specific treatment, with effective therapy currently limited to minimizing potentially harmful ventilation and avoiding a positive fluid balance. Many pharmacological therapies have been investigated with limited success to date. In this review article we provide a state-of-the-art update on recent and ongoing trials, as well as reviewing promising future pharmacological therapies in ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 40 publications
1
77
0
1
Order By: Relevance
“…7 In the present guideline, we systematically and transparently review the available evidence for fluid and drug interventions in patients fulfilling the ARDS criteria regardless of the underlying disease.…”
Section: Editorial Comment: What This Article Tells Usmentioning
confidence: 99%
“…7 In the present guideline, we systematically and transparently review the available evidence for fluid and drug interventions in patients fulfilling the ARDS criteria regardless of the underlying disease.…”
Section: Editorial Comment: What This Article Tells Usmentioning
confidence: 99%
“…3,4 Because of the high mortality rate and its substantial impact on public health, novel therapeutic approaches for ARDS are badly needed. 5 Originally based in popular use by successive generations, traditional medicine has been a source of pharmacotherapy for millions of people worldwide. [6][7][8] Plants can provide a vast source of active natural products for the discovery of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…6 There is currently no effective pharmacological therapy which targets the underlying mechanisms implicated in the development of ARDS. 7 The National Heart, Lung and Blood Institute Working Group considered the future research directions in ARDS and highlighted the lung epithelium as an important target for new therapies for ARDS. 8 Keratinocyte Growth Factor (KGF) modulates several mechanisms recognised to be important in alveolar epithelial repair 9 and therefore may be a potential therapeutic Additional mechanistic outcomes are listed in the study protocol but are not reported in this paper.…”
Section: Introductionmentioning
confidence: 99%